2020
DOI: 10.1088/1361-6463/ab7fd3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of dual-pulse laser energy deposition in a supersonic flow

Abstract: Dynamics of plasma generated by the dual-pulse laser in a supersonic flow was studied numerically. The mathematical model includes species, momentum, electronic, vibrational and translational energy equations for the multicomponent ionized air. The model examines temporal dynamics of the formed air plasma and how it affects the drag, pressure signature and vorticity generation in a supersonic flow around a wedge. We observed that nonequilibrium plasmas is more effective in the drag reduction compared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
(40 reference statements)
0
1
0
1
Order By: Relevance
“…In the early stage of DPL ignition, the laser plasma is in a nonequilibrium state because a significant part of the laser energy at an electron temperature of approximately 1 eV is spent on the vibrational excitation of nitrogen molecules. Recent results also suggest that the dualpulse-based system can ignite a mixture in turbulent flow considering an extremely high initial degree of ionization [53], enhanced flow control, and drag reduction in supersonic flows [54,55], and can support a plasma-enhanced deflagration to detonation transition (DDT) [56]. Numerical studies of DPL ignition in a frame of one-and two-dimensional (2D) threetemperature plasma models have shown that the initial electron number density pattern created by the first laser pulse can tailor the ignition kernel dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In the early stage of DPL ignition, the laser plasma is in a nonequilibrium state because a significant part of the laser energy at an electron temperature of approximately 1 eV is spent on the vibrational excitation of nitrogen molecules. Recent results also suggest that the dualpulse-based system can ignite a mixture in turbulent flow considering an extremely high initial degree of ionization [53], enhanced flow control, and drag reduction in supersonic flows [54,55], and can support a plasma-enhanced deflagration to detonation transition (DDT) [56]. Numerical studies of DPL ignition in a frame of one-and two-dimensional (2D) threetemperature plasma models have shown that the initial electron number density pattern created by the first laser pulse can tailor the ignition kernel dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…В [6] доказывается возможность плазменного воздействия на процесс обтекания тела при помощи короткоимпульсного газового разряда, который увеличивает температуру электронов, оставляя при этом неизменной температуру газа. В [7] на основе неравновесной модели двойного лазерного импульса установлено, что с увеличением степени ионизации происходит уменьшение силы сопротивления поверхности тела. Возможность воздействия на ударную волну однородной газоразрядной среды экспериментально исследована в [8].…”
unclassified